PSYCHOLOGICAL FACTORS OF MUSICAL EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article explores the intricate relationship between music education and various psychological factors, including cognitive development, emotional well-being, and academic performance. Through a comprehensive literature analysis, the study delves into the methods employed to investigate these factors, presents the results of relevant research, discusses their implications, and offers conclusions and suggestions for the advancement of music education.